The Politeness Concept of the Language Spoken by Women in Javanese Culture - Mayasari; Lubis, Ilham Sahdi; Pujiono, Mhd. (Technium Social Sciences Journal, 2021)
This study critically examines the Politeness Concept of The Language Spoken by Women in Javanese Culture related to the realization or modesty of Javanese women in speaking with other people and what factors are behind this believed concept. The method used to study this topic is to use a description of the problem based on the concept of politeness from Foley, in the form of two types of politeness in general, namely positive and negative politeness. The results of this study generally describe Javanese women who more often use positive politeness strategies than negative politeness strategies when speaking. It also causes a woman to get closer to other women more quickly or with the opposite sex she has just met than men. Negative politeness strategies are mostly used by Javanese women in expressing apology. Secondly, in this study also identified factors underlying the concept of politeness, in these factors there are stereotypes in Javanese society which place women’s gender as second sex after men and also the lack of confidence of women to express ideas or ideas as due to stereotypes in the community